Cas9-directed immune tolerance in humans—a model to evaluate regulatory T cells in gene therapy? - Dimitrios L. Wagner; Lena Peter; Michael Schmueck‐Henneresse (2021)
Abstract The dichotomic nature of the adaptive immune response governs the outcome of clinical gene therapy. On the one hand, neutralizing antibodies and cytotoxic T cells can have a dramatic impact on the efficacy and safety of human gene therapies. On the other hand, regulatory T cells (Treg) can promote tolerance toward transgenes thereby enabling long-term benefits of in vivo gene therapy after a single administration. Pre-existing antibodies and T cell immunity has been a major obstacle for in vivo gene therapies with viral vectors. As CRISPR-Cas9 gene editing advances toward the clinics, the technology’s inherent immunogenicity must be addressed in order to guide clinical treatment decisions. This review summarizes the recent evidence on Cas9-specific immunity in humans—including early results from clinical trials—and discusses the risks for in vivo gene therapies. Finally, we focus on solutions and highlight the potential role of Cas9-specific Treg cells to promote immune tolerance. As a “beneficial alliance” beyond Cas9-immunity, antigen-specific Treg cells may serve as a living and targeted immunosuppressant to increase safety and efficacy of gene therapy.